Heparin Induces Synthesis and Secretion of Tissue Factor Pathway Inhibitor from Endothelial Cells In Vitro - Hansen, John-Bjarne; Svensson, Birgit; Olsen, Randi; Ezban, Mirella; Østerud, Bjarne; Paulssen, Ruth H. (Thrombosis and Haemostasis, 2000)
TFPI is a potent inhibitor of the extrinsic coagulation system constitutively synthesized by endothelial cells. A major portion of intravascular TFPI is stored associated with endothelial cells, and administration of unfractionated heparin (UFH) in vivo causes a prompt mobilization of TFPI into the circulation. The present study was conducted to investigate how UFH affected the synthesis, secretion and anticoagulant potency of TFPI in endothelial cells in vitro. A spontaneously transformed immortal endothelial cell line was used (ECV304). Stimulation of ECV304 cells with UFH caused a prompt dose-dependent (0-5 IU UFH/ml) release of TFPI to the medium accompanied by no change of TFPI at the surface membrane assessed by immunocytochemical methods. Northern blot analysis revealed two mRNA transcripts for TFPI with a molecular size of 1.4 kb and 4.4 kb, respectively. Stimulation of ECV304 cells for 24 hrs with various concentrations of UFH caused a dose-dependent increase of TFPI in the medium (6.2-29.6 ng/106 cells within the concentration range 0-10 IU/ml). A similar dose-dependent increase in the expression of both TFPI mRNA species was observed. Long-term incubation of ECV304 cells with 5.0 IU/ml UFH caused a 5-10 fold increase in the TFPI concentration accumulated in the medium over 48 hrs. The increased TFPI mRNA expression induced by UFH appeared already after 10 min, peaked after 2-4 hrs, remained augmented throughout the entire period of UFH exposure, and preceeded the synthesis-dependent increase in TFPI release by 2-4 hrs. The procoagulant activity of the cells was downregulated by 36 % and the contribution of TFPI to the anticoagulant potency of ECV304 cells was moderately increased after 24 hrs heparin stimulation. It is suggested that these mechanisms are of major importance for the anticoagulant function of heparins.
Keywords: Endothelial cells; heparin; TFPI; anticoagulant function